Citizen Participation in Solving Issues of Local Significance: Experience of the Republic of Belarus - O. V. Efremov (Евразийская интеграция: экономика, право, политика, 2021)
The article presents a brief analysis of the legal acts of the Republic of Belarus on the participation of citizens in the discussion and solution of local affairs and the practice of their application, as well as the results of the implementation of a number of projects of international technical assistance in this area. Citizen participation in decision-making is one of the key tools for increasing public confidence in state institutions at all levels of government, reducing the level of social tension and the risk of conflict situations in the modern society. The state acquires an additional opportunity to raise its awareness of the problems, needs and expectations of the population, as well as maximize the involvement of the potential of individual citizens and civil society as a whole by enabling citizens to participate in discussions and decision-making.